APLIKASI MODEL KONSEPTUAL CARING DARI JEAN WATSON DALAM ASUHAN KEPERAWATAN - Muhlisin, Abi; Ichsan, Burhanudin (Jurnal Berita Ilmu Keperawatan, 2008)
Caring science is an orientation human science and humanity to process, phenomenon, and experience of human caring. Caring science, like also other science, covers art and humanity. Transpersonal Caring confess unity in life and relationships which there is in circle caring which is concentric - from individual, at others, at public, at world, at planet earth, at nature universe. Values caring in the theory Wastson hardly critical in maintaining humanity and increases health and process healing in practice treatment. Although caring also is elaborated in a few other treatment model, the theory human caring from Watson presents is in perpective ness is different in treatment science. The theory Watson include;covers values and factors caring relevant to guide the application of treatment process through caring transactional.